COMPOSITION AND IMPORTANT VALUE INDEX OF BIRDS IN RELATION TO STUDY OF BALI STARLING (Leucopsar rothschildi) IN THE BALI BARAT NATIONAL PARK - Wahyu Widodo (Masyarakat Zoologi Indonesia, 2014)
The aims of study were to find out the composition and important value index (IVI) of birds in Bali Barat National Park on July 2010 and June 2011. The research was in relation to study of food natural resources and artificial nest boxes of Bali Starling to reintroduce in to the wild natural habitat from captivity. The â€œPoint Transectâ€ methods were used to study bird species in the survey. There were 46 species found in the deciduous forests and 64 species in the evergreen forest habitats. According to â€œZâ€ statistical analysis there is no significant different (Î±=0.05) on the dominance index value average and important bird value index in the two forest habitats. The highest IVI were Pycnonotus goiavier reached 26.6% in the deciduous forest and 25.3% in the evergreen forest. The competitors of Bali Starling in its natural habitats for food were Pycnonotus goiavier, Orthotomus sepium and Aegithina tiphia. The competitors of Bali Starling for nesting in the available artificial nest boxes were Halcyon chloris, Megalaima lineata, Megalaima haemacephala, Chrysocolaptes lucidus, Dendrocopus macei and Parus major. The results conclude that when the Bali Starling would be released to its natural habitats from breeding population, the dominance and important value indexes of the other bird species as competitors, especially for feeding and nesting in the artificial nest boxes should be considered.Â